Trade models in the European Union - Claudius Gräbner; Dennis Tamesberger; Philipp Heimberger; Timo Kapelari; Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2019)
By studying the factors underlying differences in trade performance across European economies, this paper derives six different "trade models" for 22 EU-countries and explores their developmental and distributional implications. We first introduce a typology of trade models by clustering countries based on four key dimensions of trade performance: endowments, technological specialization, labour market characteristics and regulatory requirements. The resulting clusters comprise countries that base their export success on similar trade models. Our results indicate the existence of six different trade models: the 'primary goods model' (Latvia, Estonia), the 'finance model' (Luxembourg), the 'flexible labour market model' (UK), the 'periphery model' (Greece, Portugal, Spain, Italy, France), the 'industrial workbench model' (Slovenia, Slovakia, Poland, Hungary, Czech Republic), and the 'high-tech model' (Sweden, Denmark, Netherlands, Belgium, Ireland, Finland, Germany and Austria). Subsequently, we comparatively analyse the economic development and trends in inequality across these trade models. We observe a shrinking wage share and increasing personal income inequality in most of the trade models. The 'high-tech model' is an exceptional case, being characterised by a relatively stable economic development and an institutional setting that managed to counteract rising inequality.
Keywords: 330; trade policy; cluster analysis; European Union; trade models